Capnocytophaga canimorsus infection led to progressively fatal septic shock in an immunocompetent patient. Issue 1 (19th February 2022) - Nakayama, Ryuichi; Miyamoto, Shuichi; Tawara, Toshihiro; Aoyagi, Arisa; Oguro, Takeo; Kobayashi, Nobumichi; Suzuki, Michio; Takeyama, Yoshihiro
Abstract : Background: Capnocytophaga canimorsus infection is rare, with a high fatality rate; however, there are few cases of death with a rapid course. This study reports a progressively fatal case of C. canimorsus . Case Presentation: A 68‐year‐old immunocompetent Japanese man was bitten and scratched on his right hand by a dog 6 days before emergency transportation to the emergency room with abdominal pain, back pain, and melena. The patient developed multiple‐organ failure. Despite antibiotic therapy, transfusion, vasopressor therapy, and continuous renal replacement therapy, the patient died from uncontrolled metabolic acidosis 4.5 h after admission. Approximately 80 h after admission, blood cultures were positive for C. canimorsus . Conclusions: Capnocytophaga canimorsus infection can lead to rapid progression even in immunocompetent patients. Abstract : Gram‐negative anaerobic, rod‐shaped bacteria were identified (Gram staining; 400×).